Risk effects of near-roadway pollutants and asthma status on bronchitic symptoms in children. Issue 2 (June 2018) - Urman, Robert; Eckel, Sandrah; Deng, Huiyu; Berhane, Kiros; Avol, Ed; Lurmann, Fred; McConnell, Rob; Gilliland, Frank
Abstract : Background: Bronchitic symptoms in children pose a significant clinical and public health burden. Exposures to criteria air pollutants affect bronchitic symptoms, especially in children with asthma. Less is known about near-roadway exposures. Methods: Bronchitic symptoms (bronchitis, chronic cough, or phlegm) in the past 12 months were assessed annually with 8 to 9 years of follow-up on 6757 children from the southern California Children's Health Study. Residential exposure to freeway and non-freeway near-roadway air pollution was estimated using a line-source dispersion model. Mixed-effects logistic regression models were used to relate near-roadway air pollutant exposures to bronchitic symptoms among children with and without asthma. Results: Among children with asthma, a 2 SD increase in non-freeway exposures (odds ratio [OR]: 1.44; 95% confidence interval [CI]: 1.17, 1.78) and freeway exposures (OR: 1.31; 95% CI: 1.06, 1.60) were significantly associated with increased risk of bronchitic symptoms. Among children without asthma, only non-freeway exposures had a significant association (OR: 1.14; 95% CI: 1.00, 1.29). Associations were strongest among children living in communities with lower regional particulate matter. Conclusions: Near-roadway air pollution was associated with bronchitic symptoms, especially among children with asthma and those living in communities with lower regional particulate matter. Better characterization of traffic pollutants from non-freeway roads is needed since many children live in close proximity to this source. Abstract : Supplemental Digital Content is available in the text.